Group 3 Innate Lymphoid Cells Protect Steatohepatitis From High-Fat Diet Induced Toxicity - Hamaguchi, Masahide; Okamura, Takuro; Fukuda, Takuya; Nishida, Kensuke; Yoshimura, Yuta; Hashimoto, Yoshitaka; Ushigome, Emi; Nakanishi, Naoko; Majima, Saori; Asano, Mai; Yamazaki, Masahiro; Takakuwa, Hiroshi; et al. (Frontiers in Immunology, 2021)
Background & Aims: Emerging evidence has revealed that innate lymphoid cells (ILCs) play a key role in regulating metabolic disorders. Here, we investigated the role of group 3 ILCs (ILC3s) in the modulation of Non-alcoholic fatty liver disease (NAFLD). Methods: RORɤ gfp/gfp (RORgt KI/KI) and Rag2-/- mice with the administration of A213, RORgt antagonist, fed with a high-fat-diet (HFD) for 12 weeks, were used. We performed flow cytometry, real time PCR, and lipidomics analysis of serum and liver, and used RAW264.7 cells and murine primary hepatocytes in vitro. Results: HFD increased ILC3s and M1 macrophages in the liver, and RORgt KI/KI mice deficient in ILC3 showed significant fatty liver, liver fibrosis and significantly increased palmitic acid levels in serum and liver. In addition, administration of A213 to Rag2-/- mice caused significant fatty liver, liver fibrosis, and a significant increase in serum and liver palmitate concentrations, as in RORgt KI/KI mice. Addition of palmitc acid stimulated IL-23 production in cell experiments using RAW264.7. IL-22 produced by ILC3s inhibited the palmitate-induced apoptosis of primary hepatocytes. Conclusions: HFD stimulates IL-23 production by M1 macrophages, thus promoting ILC3 proliferation, whereas IL-22 secreted by ILC3s contributes to the upregulation of hepatic lipid metabolism and has anti-apoptosis activity.